Endothelial Dysfunction and Metabolic Disorders in Patients with Sudden Sensorineural Hearing Loss - Giada Cavallaro; Alessandra Pantaleo; Vito Pontillo; Francesco Barbara; Alessandra Murri; Nicola Quaranta (Medicina, 2023)
Sudden sensorineural hearing loss (SSNHL) is defined as a sensorineural hearing loss of 30 dB or greater on at least three contiguous audiometric frequencies occurring within a 72 h period. Although SSNHL is commonly encountered in clinical audiology and otolaryngology practice, its etiopathogenesis continues to be poorly understood. Scientific investigations have highlighted the vulnerability of cochlear microcirculation to blood flow alterations. Even mild hypoperfusion can lead to immediate dysfunction in the organ of Corti, given the heightened susceptibility of cochlear hair cells to hypoxia and ischemic damage. The purpose of this review paper is to present evidence of endothelial and vascular involvement in SSNHL and the risk factors, such as metabolic syndrome, that may negatively impact the inner ear’s vascular supply, influencing the onset pattern, incidence, and prognosis of SSNHL. By addressing these variables, we can deepen our comprehension of the mechanisms underlying SSNHL and potentially uncover strategies for prevention.